Screen time and physical activity among university students during the pandemic - Pedroso, Daniele Gonçalves; Pinheiro, Gabriela Pimentel; Silva, Talita de Cassia Raminelli da; Fernandes, Andréia Guedes Oliva (O Mundo da Saúde, 2023)
Chronic Noncommunicable Diseases represent a public health problem worldwide and are the result of a combination of different risk factors such as insufficient physical activity and excessive use of electronic devices. To identify the frequency of physical activity and the use of electronic devices and television among college students. This is a cross-sectional study with a quantitative approach carried out with 87 university students from a private Higher Education Institution in the Federal District during the second half of 2020. Data collection was performed using a structured electronic questionnaire. Descriptive statistics were used for data analysis using the Statistical Package for Social Sciences (SPSS) version 21.0 software. It was observed that 63 (72.4%) students reported practicing some type of physical activity in the last three months. Concerning the frequency of physical activity, 53 (60.9%) students reported practicing at least once a week, and 21 (24.1%) reported practicing 3 to 4 days a week. As for the use of electronic devices, it was observed that 80 (92.0%) students reported using them in their free time, the most reported time of use was 2-3 hours. There was a high frequency of use of electronic devices and insufficient practice of physical activity among university students during the COVID-19 pandemic. Therefore, it is crucial to establish interventions to promote the adoption of healthy lifestyle habits for this group.